The epidemiology of childhood psoriasis: a scoping review - Burden-Teh, Esther; Thomas, Kim S.; Ratib, Sonia; Grindlay, Douglas J.C.; Adaji, Enemona; Murphy, Ruth (Wiley, 2016)
Psoriasis is an inflammatory noncommunicable skin disease that affects both adults and children. At present, the epidemiology and natural history of psoriasis are not widely understood. This scoping review aimed to map the existing literature on the epidemiology of childhood psoriasis, identify research gaps for future studies and provide a comprehensive, clinically useful review. Search strategies were developed for Ovid Medline, Ovid Embase, Google Scholar and hand searching. In total, 131 articles met the inclusion criteria and were mapped; 107 articles were included for data extraction. Over the last 25 years there has been a dramatic increase in the volume of published observational epidemiological studies on childhood psoriasis. The majority were case series or cross-sectional studies, concentrated in Europe, Asia and North America. The prevalence of childhood psoriasis was found to be higher in European countries, older children and girls. Up to 48·8% of children had a family history of psoriasis in a first-degree relative. The most frequent subtype was plaque psoriasis and the most common initial sites of presentation were the scalp, limbs and trunk. Specific genetic differences have been found between child-onset and adult-onset populations. Case–control and cohort studies investigating risk factors for psoriasis onset, comorbidities and long-term health outcomes were extremely limited. The choice of study design and heterogeneity in methodology limit the validity and generalizability of the information, consistency of the results, and comparability of the studies. Well-designed epidemiological studies are needed to provide precise and consistent information about the frequency and clinical presentation, risk factors, associated diseases and long-term outcomes in childhood psoriasis.